Pola Variasi Bahasa Jawa (Kajian Sosiodialektologi pada Masyarakat Tutur di Jawa Tengah - Endang Kurniati; Hari Bakti Mardikantoro (Humaniora, 2010)
Language use is determined not only by linguistic factors but also by nonlinguistic factors, i.e. social and situational factors. This study focuses on the variation pattern of Javanese as the expression of different social factors. Variation of Javanese language in Central Java might happen in various aspects, i.e. honology, lexicon, pengkramaan symptom, pengokoan symptom, and morphemic process. Such social factors as education, age, and occupation have an effect on the realization of Javanese language.